Decolonizing social sciences in Suriname: a strategic view in favor of regionalism - Jack K Menke; Henk E Menke (Sustentabilidade em Debate, 2015)
Social sciences research about Suriname is euro-centric. It is dominated by the Dutch and evolved in the context of academic colonialism. From the Surinamese point of view, this situation is undesired. Some lessons can be learned from others, e.g. South East Asian and New Zealand/Maori scientific communities. In order to decolonize research it is suggested that the Surinamese social scientists community is strengthened and that cooperation with institutions in the South-American and Caribbean region is intensified. To achieve sustainability in a regional context concerted action of social scientists and academic institutions is required. The focus in this article is on cooperation with Brazil, the Southern neighbor of Suriname and a leading nation in the region. Referring to common factors in history and current social developments in Suriname and Brazil, it is suggested that the cooperation that started in the last decades of the 20th century is intensified.